ANALYSIS OF HANYU JIAOCHENG TEXTBOOK USED BY THE EIGHTH-GRADE STUDENTS AT KALAM KUDUS JUNIOR HIGH SCHOOL BANDUNG - Forienka Carrin Natasha, Kezia; Selvia (Jurnal PAJAR (Pendidikan dan Pengajaran), 2023)
Mandarin is the second international language that is widely studied at several schools. Mandarin is unique such as its tone, the Han character, and how it is pronounced. In learning a language, the appropriate textbooks are needed based on the learner’s level. Several schools put Mandarin as intra-curricular and extra-curricular activities, one of which is Kalam Kudus Junior High School in Bandung, It is aimed to target students to have four basic language skills, reading, listening, writing, and speaking with balanced competence. It is required for students to be able to recognize Han characters indeed. This paper focuses on the analysis of the use of the Hanyu Jiaocheng textbook at grade 8 of Kalam Kudus Junior High School in Bandung. This paper uses qualitative research methods with data collection techniques in the form of interviews, questionnaires, and direct observation. Based on the research conducted by the author, it was found that the Hanyu Jiaocheng textbooks used in Kalam Kudus Junior High School Bandung were still not relevant to the objective determined by the school because the textbooks did not contain listening exercises. In addition, teachers and students were difficult to use the textbooks because the textbooks use the English language version as the descriptions. The authors expect that this paper can provide input or suggestions for the school principal to review the Chinese textbooks used to improve the learning process of Mandarin in the future.